Corrosion fatigue crack delayed mechanism of 60 mm Ti alloy welded joints based on the plastic and deformation coordination - Bo Li; Tao Yang; Long Lin; Jiang Yu; Yuan Zhuang; Lin Li; Xijian Su (Journal of Materials Research and Technology)
The corrosion fatigue crack propagation mechanism in thick plate titanium (Ti) alloy joints is significantly influenced by microstructural inhomogeneity, which arises from non-equilibrium solidification during welding. Clarifying the mechanism is critical for enhancing the service safety of such joints. This study aims to enhance grain plasticity and intergranular deformation coordination of the 60 mm thick plate Ti alloy joint based on regulating the dynamic microstructure evolution process, resulting in delaying the corrosion fatigue crack growth rate (FCGR). The relevant research results are indicated as follows: there was high plastic deformation work in the weld bottom layer (BL) under the function of fine grain strengthening and network dislocation distribution. The proportion of the above-mentioned region corresponding to the maximum schmidt factor with a geometric compatibility factor (SF m’) higher than 0.5 reached 32.8 %, which presented better deformation coordination. The superior plastic deformation within individual grains allows for more effective dissipation of stress concentrations, while the better coordination of deformation across grain boundaries reduces localized strain accumulation. This synergy mitigates crack tip stress and promotes a more uniform distribution of plastic strain, thereby hindering fatigue crack growth.